The tongue morphology of Pteropus vampyrus from Timor Island, Indonesia: New insights from scanning electron and light microscopic studies - YULFIA NELYMALIK SELAN; HEVI WIHADMADYATAMI; ARIS HARYANTO; DWI LILIEK KUSINDARTA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Selan YN, Wihadmadyatami H, Haryanto A, Kusindarta DL. 2023. The tongue morphology of Pteropus vampyrus from Timor Island, Indonesia: New insights from scanning electron and light microscopic studies. Biodiversitas 24: 3512-3518. The large flying fox (Pteropus vampyrus Linnaeus, 1758) is a Southeast Asian megabat species includes with frugivorous bats. The tongue plays a pivotal role in taking, chewing, and swallowing food. The structure of the bat tongue hampers considerable variation, mainly in the papilla. Variations occur owing to the feeding habits, environment, and adaptation of bats to their environments. The aim of this study was to clarify the morphological structure of the tongue of P. vampyrus obtained from the island of Timor, East Nusa Tenggara, Indonesia, by using Scanning Electron Microscope (SEM) and Light Microscopy(LM). This study included six adult bats regardless of sex. Macroscopically, the tongue of P. vampyrus consists of three parts: the apex, corpus, and radix. SEM and LM confirmed that the apex presents filiform papillae of several subtypes, including scale-like filiform, giant trifid, and small crown-like papillae. In addition, the apex features fungiform and transitional papillae between the giant trifid and small crown-like papillae. Furthermore, the corpus consists of filiform papillae (leaf-like filiform and large crown-like papillae) and fungiform papillae. The radix consists of filiform papillae (long conical, leaf-like filiform, and short conical papillae), fungiform papillae, and three V-shaped circumvallate papillae pointing to the larynx.